QAS 2022
DOI: 10.47750/qas/23.186.18
|View full text |Cite
|
Sign up to set email alerts
|

Social Performance of Islamic Banks in South-East Asia: Is Intellectual Capital and Sharia Supervisory Boards Matters?

Abstract: This study aimed to examine Islamic banks' social performance by considering the effect of Intellectual Capital (IC) and Shariah Supervisory Boards (SSB) aspects which are SSB educational background and SSB gender diversity. This study employed longitudinal sample of Islamic banks in South-east Asia region with a sample of 32 Islamic banks during the period 2005-2020. To test the research hypotheses, panel data regression model analysis was applied. The findings revealed that intellectual capital has a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Several previous studies have explained that a company's competitive advantage can be associated with corporate social performance (Greening & Turban, 2000;Gregory et al, 2016). From an Islamic banking perspective, previous research (Fatah et al, 2022;Nawaz & Haniffa, 2017;Pratama et al, 2020Pratama et al, , 2021Pratama et al, , 2022Setianto & Sukmana, 2016) has shown that IC has a positive impact on Islamic banking performance. Based on the description above, the hypothesis proposed in this study is as follows: H1: Intellectual capital has a positive effect on the Social Performance of Islamic Banks…”
Section: Literature Review and Hypothesis Development The Effect Of I...mentioning
confidence: 98%
“…Several previous studies have explained that a company's competitive advantage can be associated with corporate social performance (Greening & Turban, 2000;Gregory et al, 2016). From an Islamic banking perspective, previous research (Fatah et al, 2022;Nawaz & Haniffa, 2017;Pratama et al, 2020Pratama et al, , 2021Pratama et al, , 2022Setianto & Sukmana, 2016) has shown that IC has a positive impact on Islamic banking performance. Based on the description above, the hypothesis proposed in this study is as follows: H1: Intellectual capital has a positive effect on the Social Performance of Islamic Banks…”
Section: Literature Review and Hypothesis Development The Effect Of I...mentioning
confidence: 98%
“…Hence, there is an emphasis on high standards of education and training in Islamic banking to effectively contribute to the social performance of Islamic banks. In addition, Sharia Supervisory Board members are expected to have skills, know-how and experience in the fields of shariah, accounting and finance, which is important for addressing sharia issues and economic challenges (Pratama et al, 2022). The human capital in Islamic banking differs from conventional banking in terms of the specific expertise and knowledge required for shariah compliance, as well as the unique regulatory framework governing Islamic financial institutions (Ali and Kasim, 2019).…”
Section: Human Capital and Islamic Bankingmentioning
confidence: 99%
“…, 2021; Ousama et al. , 2020; Pratama et al. , 2022), honesty, transparency, trustworthiness, personal development based on worship, faith, science, charity and missionary endeavor, high integrity, application of values of justice (Supriyatni, 2021; Suryadi et al.…”
Section: Human Capital and Islamic Bankingmentioning
confidence: 99%
See 2 more Smart Citations